International migration, ethnicity and economic inequality - Martin Kahanec; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2008)
While the allocative efficiency of mobility is typically considered to be positive but small in the long run, the induced changes in equality may be considerable in size. In practice, however, migrants typically improve their income position in comparison to those at home, stimulate the economic situation of the sending countries through remittances and rise the economic performance of natives and of capital in the host country through complementarities. The chapter suggests that at least skilled immigration promotes economic equality in the host country under standard conditions. The context is empirically documented und theoretically explained in a core model. Also, immigrant assimilation and selection is discussed, as is the role of ethnicity and ethnic identity for relative economic performance.
urn:nbn:de:101:1-2008042170
Keywords: D33; 330; Inequality; income distribution; migration; ethnicity; minority; assimilation; integration; ethnosizing; Gini-coefficient; Internationale Wanderung; Qualifikation; Ethnische Gruppe; Einkommensverteilung; Einwanderung; Soziale Integration; Soziale Ungleichheit; Rücküberweisung (Migranten); Theorie; USA